Use of a Long-Acting Opioid Microsphere Formulation to Overcome Difficulties in Swallowing Pain Medication - Anderson N; Gillman AG; Wasan AD (Journal of Pain Research, 2020)
Nathan Anderson,1 Andrea G Gillman,1 Ajay D Wasan1,2 1Department of Anesthesiology and Perioperative Medicine, University of Pittsburgh School of Medicine, Pittsburgh, PA, USA; 2UPMC Pain Medicine, Pittsburgh, PA, USACorrespondence: Ajay D Wasan Tel +1 412 665 8048Fax +1 412 665 8033Email wasanad@upmc.eduPurpose: Xtampza ER® (XER) is a long-acting oxycodone formulation which was designed to be abuse-deterrent and to overcome capsule-swallowing issues. This pilot study evaluated the effectiveness of XER at reducing swallowing difficulty while providing effective analgesia in the setting of chronic pain.Subjects and Methods: Eleven subjects with chronic pain who reported pill-swallowing difficulty were enrolled in a 6-week uncontrolled open-label pilot study in which their prescribed daily opioid medication was converted to XER. Swallowing difficulty, pain intensity, opioid satisfaction, and secondary indicators of pain response were recorded for subjects throughout the study.Results: Both swallowing difficulty and opioid satisfaction (XER vs baseline opioid) improved significantly over the 6-week study period (p < 0.05), while pain intensity ratings demonstrated no significant change. No significant change was noted in any of the secondary pain, mental health, or physical function measures after conversion to XER compared to baseline.Conclusion: Subjects experienced improvement in both swallowing and opioid medication satisfaction after conversion to XER with no significant change in pain intensity and related measures.Keywords: opioid medication, swallowing difficulty, chronic pain, abuse deterrent formulation